2016
DOI: 10.1111/bcp.13131
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of daptomycin in adult patients undergoing continuous renal replacement therapy

Abstract: AimThe objective of this population pharmacokinetic (PK) analysis was to provide guidance for the dosing interval of daptomycin in patients undergoing continuous renal replacement therapy (CRRT).MethodsA previously published population PK model for daptomycin was updated with data from patients undergoing continuous veno‐venous haemodialysis (CVVHD; n = 9) and continuous veno‐venous haemodiafiltration (CVVHDF; n = 8). Model‐based simulations were performed to compare the 24 h AUC, C max and C min of daptomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…Daptomycin at 8 mg/ kg q48h in patients receiving CVVHD achieved higher peak and lower trough concentrations compared with 4 mg/kg q24h, which maximize daptomycin's concentration-dependent activity and minimize the risk of myopathy (Vilay et al, 2011). A higher dosage regimen (8 mg/kg q24h) was shown to be appropriate for patients during CVVHDF (Xu et al, 2017). However, a recent study found that 8 mg/kg q24h daptomycin has a high probability of reaching the toxicity-related concentration threshold, while 6 mg/kg q24h gave a satisfactory risk-benefit balance during CVVHDF or CVVHD (Xie et al, 2020).…”
Section: Daptomycinmentioning
confidence: 94%
See 1 more Smart Citation
“…Daptomycin at 8 mg/ kg q48h in patients receiving CVVHD achieved higher peak and lower trough concentrations compared with 4 mg/kg q24h, which maximize daptomycin's concentration-dependent activity and minimize the risk of myopathy (Vilay et al, 2011). A higher dosage regimen (8 mg/kg q24h) was shown to be appropriate for patients during CVVHDF (Xu et al, 2017). However, a recent study found that 8 mg/kg q24h daptomycin has a high probability of reaching the toxicity-related concentration threshold, while 6 mg/kg q24h gave a satisfactory risk-benefit balance during CVVHDF or CVVHD (Xie et al, 2020).…”
Section: Daptomycinmentioning
confidence: 94%
“…Ultrafiltration rate: 14-23 ml/min 250 mg q24h (Malone et al, 2001) Not suitable as monotherapy to treat gramnegative infections (Shaw and Mueller, 2017) Dialysate rate: 0.8-1.5 ml/min, Ultrafiltration rate: 9-23 ml/min 250 mg q24h (Malone et al, 2001) Ciprofloxacin Ultrafiltration rate: 30 ml/kg/h 400 mg q8h (Roger et al, 2016a) Dialysate rate: 3 L/h 200 mg q8h (Wallis et al, 2001) Dialysate Loading dose: 15-20 mg/kg Maintenance dose: 500 mg (7.5-10 mg/kg) q24h (Matsumoto et al, 2013) Teicolanin Loading dose: 1,200 mg Maintenance dose: 600-1,800 mg q24h (Bellmann et al, 2010) Dialysate rate: 16 ml/min Loading dose: 800 mg Maintenance dose: 400 mg q48-72h (Wolter et al, 1994) -Daptomycin -Dialysate rate >30 ml/kg/h 6 mg/kg q24h (Corti et al, 2013;Xie et al, 2020) Combined flow rate >30 ml/kg/h 6-8 mg/kg q24h (Corti et al, 2013;Xu et al, 2017;Xie et al, 2020)…”
Section: B) Levofloxacinmentioning
confidence: 99%
“…Daptomycin is a lipopeptide characterized by concentration-dependent activity, high protein binding, and low V; despite a low f, the CL EC in CVVHD was reported as relatively high compared to nonrenal CL, resulting in a significant EC fractional CL (around 50%) (68). Although the suggested maintenance dose may vary according to dialysis intensity and modality, a daily dose ranging from 8 to 12 mg/kg has been recently suggested to avoid underdosing (69,70). Otherwise, in patients receiving thrice-weekly IHD, administration of daptomycin (4 to 6 mg/kg) thrice weekly after each IHD session appears to be safe and effective, with a 50% increased dose (from 6 to 9 mg/kg) being suggested at the end of IHD session preceding the long interdialytic period (71).…”
Section: Glyco- Glycolipo- and Lipopeptidesmentioning
confidence: 99%
“…Diese Ergebnisse wurden jüngst erneut bestätigt, wobei hier ergänzend gezeigt wurde, dass Dosen von 6 mg/kgKG bei einigen Patienten nicht ausreichend sind, sodass zusammenfassend eine Einmalgabe von 6-8 mg/kgKG unter einer standardisierten und wirklich kontinuierlichen CRRT-Therapie als effektiv und sicher empfohlen werden kann [27].…”
Section: Merkeunclassified